2020
DOI: 10.1007/s10552-019-01258-z
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation and benign breast disease in a cohort of U.S. women

Abstract: Purpose-Several studies indicate that sexual minority (e.g., bisexual, lesbian) women may be at an increased risk for breast cancer. However, we know little about how risk factors, such as benign Terms of use and reuse: academic research for non-commercial purposes, see here for full terms. https://www.springer.com/aamterms-v1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…55 Higher rates of several risk factors for breast cancer, including nulliparity, obesity, and alcohol use, may contribute to this disparity. 56 Lower rates of preventive care likely contribute as well, as SMW are more likely to seek mammograms in response to symptoms rather than for routine screening, leading to delays in presentation to care. 57 Breast surgical oncologists should understand the factors that contribute to higher mortality rates from breast cancer in SMW.…”
Section: While Factors That Contribute To Oncologic Disparities Inmentioning
confidence: 99%
“…55 Higher rates of several risk factors for breast cancer, including nulliparity, obesity, and alcohol use, may contribute to this disparity. 56 Lower rates of preventive care likely contribute as well, as SMW are more likely to seek mammograms in response to symptoms rather than for routine screening, leading to delays in presentation to care. 57 Breast surgical oncologists should understand the factors that contribute to higher mortality rates from breast cancer in SMW.…”
Section: While Factors That Contribute To Oncologic Disparities Inmentioning
confidence: 99%
“…(31,33) According to the WHI, LBW have a higher prevalence of breast cancer compared to heterosexual women. (34,35) When the literature is examined, different study results related to the subject were found. The study of Boehmer et al (10) reported that in the 2001, 2003, 2005, and 2007 California Health Interview Surveys, the lesbian population density was associated with higher breast cancer incidence, and the executive bisexual population density was associated with lower breast cancer incidence.…”
Section: Breast Cancermentioning
confidence: 99%